Clinical Benefit‐Risk Assessment of Nivolumab 240 mg Every 2 Weeks in Chinese Patients With Advanced and Metastatic Solid Tumors. (14th February 2021) - Sheng, Jennifer; Zhang, Jason; Baudelet, Christine; Roy, Amit
Abstract: Nivolumab 240 mg every 2 weeks is approved in China by the National Medical Product Agency for squamous cell carcinoma of the head and neck and gastric cancer, based on population pharmacokinetic (PPK) analyses and benefit‐risk assessment of safety/efficacy in solid tumors, including Chinese and global populations. The aim of this assessment was to investigate exposure and risk for adverse events (AEs) with flat dosing compared with weight‐based dosing. Nivolumab 240‐mg and 3‐mg/kg every‐2‐week exposures in Chinese patients were simulated using PPK modeling, and AEs in Chinese and pooled global populations were compared by dosing regimen, exposure, and weight. The 10‐mg/kg every‐2‐week regimen was included because it is known to be well tolerated. Predicted nivolumab exposure in Chinese patients receiving 240 mg every 2 weeks was ∼25% higher versus 3 mg/kg every 2 weeks, but ∼60% lower versus 10 mg/kg every 2 weeks. Grade 3/4 AE incidence in Chinese patients receiving nivolumab 3 mg/kg every 2 weeks was similar with 240‐mg every‐2‐week dosing and with patients from global populations treated with 3 or 10 mg/kg every 2 weeks. There was no trend toward increased AE incidence with high versus low nivolumab exposure or in global patients of varying body weight receiving 3 or 10 mg/kg every 2 weeks. Objective response rates were similar in Chinese and global patients with squamous and nonsquamous NSCLC. Results showed that benefit‐risk profiles with nivolumab 240 mg every 2 weeks were similar to those of the 3‐mg/kg every‐2‐week regimen in Chinese patients and global populations, providing an alternative treatment option to Chinese patients.